2016
DOI: 10.1007/s00449-016-1649-y
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput system for screening of high l-lactic acid-productivity strains in deep-well microtiter plates

Abstract: For strain improvement, robust and scalable high-throughput cultivation systems as well as simple and rapid high-throughput detection methods are crucial. However, most of the screening methods for lactic acid bacteria (LAB) strains were conducted in shake flasks and detected by high-performance liquid chromatography (HPLC), making the screening program laborious, time-consuming and costly. In this study, an integrated strategy for high-throughput screening of high L-lactic acid-productivity strains by Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Moreover, computation fluid dynamics (CFD) has been proven to be a powerful tool for flow field prediction, design and scale‐up of bioreactors . CFD simulation can characterize the flow field, power consumption, mass transfer, shear and mixing simultaneously, and CFD applications on miniature bioreactors are also well documented …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, computation fluid dynamics (CFD) has been proven to be a powerful tool for flow field prediction, design and scale‐up of bioreactors . CFD simulation can characterize the flow field, power consumption, mass transfer, shear and mixing simultaneously, and CFD applications on miniature bioreactors are also well documented …”
Section: Introductionmentioning
confidence: 99%
“…Tan et al (2014) used a novel and effective mixture culture method, and performed a high-throughput screening of realized the whole mutant library of Monascus purpureus. An integrated strategy for high-throughput screening of high l-lactic acid-productivity strains in deep-well microtiter plates (MTPs) was developed by Lv et al (2016). And they confirmed that 24-well U-bottom MTPs could well alternate shake flasks for cell cultivation as a scale-down tool.…”
Section: Discussionmentioning
confidence: 87%
“…High-throughput screening technologies playa key role in reaching for improved strains, which is large scale, low cost, and high specificity (Ottenheim et al 2018;Zhang et al 2018). Highthroughput screening technologies consist in generating a mutant library in high-throughput miniaturized cultivation platforms, such as microplates (Tan et al 2013), shake flasks, micro-bioreactors (Tian et al 2018), and using a high-throughput detection platform (Tan et al 2014;Lv et al 2016). Unlike previous reported studies, which only focused on single target of product titer or productivity, the present study characterized two indexes for the production of high SLs contents by coutilizing glucose and glycerol capacity.…”
Section: Introductionmentioning
confidence: 99%
“…For 96-well MTPs, the mutants were inoculated in 96-well MTPs with 100 mL liquid screening medium in each well at 200 rpm shaking for 12 h. For shake asks, the method was detailed in our previous work. 31…”
Section: Culture Conditionsmentioning
confidence: 99%